مدى توافر معايير جودة الأداء التدريسي لدى معلمي الرياضيات - عبد الله أحمد القحفة, أحمد; أحمد مرشد القواس, محمد (جامعة الوادي - University of Eloued, 2020)
هدف البحث إلى تحديد مستوى توافر معايير جودة الأداء التدريسي لدى معلمي الرياضيات بمديرية النادرة، تكونت بطاقة الملاحظة من (120) معيارً موزعة في ستة عشرة محور، تم تطبيق أداة البحث على عينة تكونت من (100) أستاذ وأستاذة من مدرسي الرياضيات، وبعد الانتهاء من تطبيق أداة البحث تم جمع البيانات وتحليلها، وقد أسفرت النتائج عن تحقيق (7) معايير المستوى (عال جدً)، و(55) المستوى (عال)، و(52) المستوى (متوسط)، و(5) المستوى (مقبول)، ومعيار واحد المستوى (ضعيف)، وهذا يعني أن المحاور جميعا قد حققت مستوى متوسط وما فوق، وأن جودة أداء الكفايات التدريسية لدى معلمي الرياضيات متوسطة توزعن بين متوسطي(4.53 – 1.56)، وقد أوصى الباحث بحاجة معلمي الرياضيات إلى تطوير الأداء التدريسي بشكل عام، واقترح تنفيذ دراسات أخرى مشابهه. Abstract: The research aimedatdet ermining the level of the availability of quality standards of teaching performancequalityamong Mathematic steachers in Al-Nadira District. The researchtool, (observation card) which was made up of (120) standards distributed in sixteen axes, was applied on a sample consisting of (100) teachers (males and females) of Mathematics ,After the completion of the application of the researchtool, data was collected and analyzed. The results have shown the achievement of 7 standards the level (veryhigh), 55 the level (high), 25 the level (intermediate), 5 the level (accepted) and one standard the level (weak). This meansthat all the axes have achieved an intermediatelevel and aboveintermediate, and that the quality of teaching performancecompetenciesamongMathematicsteacherswasntermediatedistributedbetween the averages (1.56-4.53). The researcherrecom mended the need of Mathematic steachers to develop the teaching performance in general, and the ysuggested the implementation of other similarstudies.
بمديرية النادرة الجمهورية اليمنية
مقال
Keywords: الأداء التدريسي, الكفايات التدريسية, معايير الجودة; Teaching Performance; Teaching Competencies; Quality Standards